Influence of impurity on the life period of the charge in silicon single crystals - Головко, Олександр Костянтинович (Technology audit and production reserves, 2012)
In article on the basis of experimental researches it is established, that on the life period of the nonequilibrium charge carriers in the silicon single crystals which has been growing in industrial conditions, the greatest influence renders the ratio of concentration of impurity of oxygen and carbon